ВПРОВАДЖЕННЯ В НОРМАТИВНУ БАЗУ УКРАЇНИ ЄВРОПЕЙСЬКИХ ВИМОГ ДО ПРОВЕДЕННЯ ВИМІРЮВАННЯ ПОКАЗНИКІВ ЯКОСТІ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ - Жаркін, А.Ф.; Палачов, С.О. (Інститут електродинаміки Національної академії наук України, 2023)
The analysis of the main European requirements and provisions of the EN 50160:2022 concerning the correct choice of the point of measurement of power quality characteristics was carried out, and the relation between the power quality requirements and EMC compatibility levels was shown. The main differences in the principles of organization of measurement of power quality characteristics adopted in Ukraine and their compliance with modern European principles were studied. References 4, figures 1, tables 1.